PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. MEGA FINANCE CABANG KANDIS KABUPATEN SIAK - Anuar, Saiful (Eko dan Bisnis: Riau Economic and Business Review, 2020)
The purpose of this study was to determine the influence of work discipline on employee performance at PT. Mega Finance Cabang Kandis Kabupaten Siak. The sample in this research is all employee at PT. Mega Finance Cabang Kandis Kabupaten Siak which amounts to 45 people. Sampling was conducted using a sample of saturated (Sugiyono, 2010:96) "sampling saturated sampling technique when all members of the population used as a sample". While the variables studied in this research is the discipline of work and performance.Analysis of data using simple linear regression method using validity test, reliability test, normality, t test and R2. The tests are conducted to determine the relationship between the independent variables (independent variables) and dependent variable (dependent variable). Based on the results obtained value R-square at 0,711 which means that the discipline of work has contributed a donation of 71,1% to performance employees at PT. Mega Finance Cabang Kandis Kabupaten Siak. Partially acquired discipline of work variableÂ  positive and significant impact on the performance employees at PT. Mega Finance Cabang Kandis Kabupaten Siak with simple linear regression equation in this study :Y = 4,954 + 0,738X significantly 0,000 smaller than alpha of 0.05. The final conclusion of this study that partial hypothesis between variables proven discipline of work to performance employees and can be accepted as true.